1994
DOI: 10.1111/j.1476-5381.1994.tb14033.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological analysis of neutrophil chemotactic factor production by leucocytes and roles of PAF in allergic inflammation in rats

Abstract: 1 The role of platelet activating factor (PAF) in neutrophil infiltration in air pouch type allergic inflammation in rats was investigated. 2 Neutrophil infiltration into the pouch fluid 8 h after injection of the antigen (azobenzenearsonateconjugated acetyl bovine serum albumin) solution into the air pouch of immunized rats was inhibited dose-dependently by treatment with PAF antagonists 180) in parallel with the decrease in neutrophil chemotactic activity in the pouch fluid. 3 Four hours after injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Neutrophil chemotactic activity in the diluted supernatant fraction of the conditioned medium was assayed using modified Boyden chambers as described previously (Watanabe et al, 1994).…”
Section: Measurement Of Neutrophil Chemotactic Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Neutrophil chemotactic activity in the diluted supernatant fraction of the conditioned medium was assayed using modified Boyden chambers as described previously (Watanabe et al, 1994).…”
Section: Measurement Of Neutrophil Chemotactic Activitymentioning
confidence: 99%
“…infiltrated into the pouch fluid in the allergic inflammation model are much more active than those in the non-allergic inflammation model with respect to neutrophil chemotactic factor production. When the infiltrated leucocytes in the pouch fluid were collected 4 h after injection of the antigen solution and incubated, leucocytes from the immunized rats produced a larger amount of neutrophil chemotactic factors than did leucocytes from the non-immunized rats, thereby suggesting that the leucocytes infiltrated into the pouch fluid in the immunized rats are much more active than those in the non-immunized rats (Watanabe et al, 1994). Our present investigation was intended to clarify pharmacologically the mechanism of activation of leucocytes for the production of neutrophil chemotactic factors in the allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PAF has been implicated as a potent chemical mediator of inflammation and allergy. We reported (Watanabe et al, 1990;1994) that several PAF antagonists inhibit neutrophil infiltration in the allergic inflammation model in rats and suggested that PAF plays a significant role in neutrophil infiltration.…”
Section: Introductionmentioning
confidence: 99%